Intensitas Penggunaan Media Sosial Terhadap Kecemasan Sosial Pada Remaja - kansil, aprillia; Deetje J. Solang; Mike A. K. Lovihan (Universitas Darul Ulum, 2025)
The rapid development of digital technology has changed the pattern of adolescent sosial interaction, particulary in social media use. Sosial media can have both positve and negative impacts on adolescent psychological development, one of which is sosial anxiety. This study aims to analyze the effect of social media use intensity on social anxiety among adolescent aged 16 – 18 years. The research method used a quantitative. The research subjects consisted of 235 high school students selected using purposive sampling technique. The research intruments were social media use intensity scale and social anxiety scale that had been tested for validity and reliability. Data analysis technique used simple linear regression analysis with SPSS V29 program. The results showed that there was a significant positive effect between the intensity of social media use on social anxiety in adolescent.